Sex-dependent alteration of cardiac cytochrome P450 gene expression by doxorubicin in C57Bl/6 mice. Issue 1 (December 2017) - Grant, Marianne; Seelig, Davis; Sharkey, Leslie; Zordoky, Beshay
Abstract Background There is inconclusive evidence about the role of sex as a risk factor for doxorubicin (DOX)-induced cardiotoxicity. Recent experimental studies have shown that adult female rats are protected against DOX-induced cardiotoxicity. However, the mechanisms of this sexual dimorphism are not fully elucidated. We have previously demonstrated that DOX alters the expression of several cytochrome P450 (CYP) enzymes in the hearts of male rats. Nevertheless, the sex-dependent effect of DOX on the expression of CYP enzymes is still not known. Therefore, in the present study, we determined the effect of acute DOX exposure on the expression of CYP genes in the hearts of both male and female C57Bl/6 mice. Methods Acute DOX cardiotoxicity was induced by a single intraperitoneal injection of 20 mg/kg DOX in male and female adult C57Bl/6 mice. Cardiac function was assessed 5 days after DOX exposure by trans-thoracic echocardiography. Mice were euthanized 1 day or 6 days after DOX or saline injection. Thereafter, the hearts were harvested and weighed. Heart sections were evaluated for pathological lesions. Total RNA was extracted and expression of natriuretic peptides, inflammatory and apoptotic markers, and CYP genes was measured by real-time PCR. Results Adult female C57Bl/6 mice were protected from acute DOX-induced cardiotoxicity as they show milder pathological lesions, less inflammation, and faster recovery from DOX-induced apoptosis and DOX-mediated inhibition of beta-type natriuretic peptide. Acute DOX exposure altered the gene expression of multiple CYP genes in a sex-dependent manner. In 24 h, DOX exposure caused male-specific induction of Cyp1b1 and female-specific induction of Cyp2c29 and Cyp2e1. Conclusions Acute DOX exposure causes sex-dependent alteration of cardiac CYP gene expression. Since cardiac CYP enzymes metabolize several endogenous compounds to biologically active metabolites, sex-dependent alteration of CYP genes may play a role in the sexual dimorphism of acute DOX-induced cardiotoxicity.